PSYCHOLOGICAL CONDITIONS OF PERSONALITY FORMATION (Conferencea, 2023)
The beginning of another approach to understanding the concept of psychological health was laid by Z. Freud, who, as you know, understood many mental illnesses as a result of personal internal conflicts that disturb even healthy people. He believed that the whole range of negative emotional experiences (depression, anxiety, etc.) is the subjective side of these conflicts that arise when the goals set by a person and the means of achieving them conflict with each other.As a result, in the following decades, human mental health became the research object of other sciences about man and society, first of all, psychology. A person's psychological health is related to personal characteristics that combine all aspects of a person's inner world and ways of its external manifestation into a single whole. Psychological health, on the one hand, is an important component of a person's social well-being, and on the other hand, his vitality.